The prospect of distance education in Ukraine - Shurdenko, Maria (Lviv Polytechnic Publishing House, 2015)
The article is headlined of distance learning. Distance learning is defined as a kind of open learning using computer and telecommunication facilities that provide interactivity teachers and students at different stages of training and individual work with the latest materials information network, most of which prepared teachers. The purpose of our publication is to highlight trends of distance education in modern society and focus on the advantages and disadvantages of distance learning. The article goes on to say that distance дearning this kind of educational services is gaining popularity worldwide. Analysis of distance education shows that all institutions, organizations and agencies that implement or use of distance learning technologies, encounter real difficulties to overcome which requires targeted financing, joint efforts with the efforts of schools of public authorities, coordination of joint actions and regulatory and legal software that will help accelerate the process.
Keywords: distance learning; e-learning; educational space; information education; learning platforms